Optimization of Self-Micro Emulsifying Drug Delivery System) for Soursop Leaf (Annona muricata Linn.) Chloroform Extract - Anif Nur Artanti; Fea Prihapsara; Dian Eka Ermawati; Aprilia Saefanan Shofa (Majalah Obat Tradisional, 2020)
Soursop leaf chloroform extract has anticancer activity.  The active ingredient of soursop leaf was acetogenin polypoid derivatives that have a lipophilic characteristic, and less effective to achieve action targets of drugs in biological systems. The Self-Micro Emulsifying Drug Delivery System (SMEDDS) was an effective drug delivery technique that increases the solubility of lipophilic drugs. This study aims to determine the proportion of optimum SMEDDS formula using Simplex Lattice Design (SLD) method. The Formula of SMEDDS was prepared using a combination of Tween 80-Croduret, Propylene Glycol, and Candlenut oil. Optimization formula with SLD method using Design-Expert software based on physical stability parameters there are the percent of transmittance and emulsification time. The optimum formula of SMEDDS was compared with SLD prediction formula using a statistical analysis t-test, then test of loading dose extract, stability test accelerated by centrifugation, particle size, and zeta potential. The proportion of optimum composition of Tween 80-Croduret, Propylene Glycol, and Candlenut oil of SMEDDS was 60.87%; 24.13%; 15.00% respectively. Results of transmittance 41.14±3.78% and emulsification time 119.0±2.08 seconds. The predicted SLD value for the transmittance percent was 55.0% and the emulsification time was 119.59 seconds. The result of the statistical analysis of one sample t-test showed no significant difference between observation results and SLD prediction. The SMEDDS system has F value of 0.99 and capable to load 25.0 mg chloroform extract of soursop leaf each system with an average particle size of 440 nm and zeta potential of +21.5 mV.